Cyclic tetra[(indolyl)-tetra methyl]-diethane-1, 2-diamine (CTet) impregnated hydrous zirconium oxide as a novel hybrid material for enhanced removal of fluoride from water samples1. Issue 49 (30th May 2015) - Rahman, Nafisur; Haseen, Uzma; Khan, Mohammad Fazeel
<x xml:space="preserve">Abstract</x> A hybrid material was prepared by incorporating cyclic tetra[(indolyl)-tetra methyl]-diethane-1, 2-diamine (CTet) into hydrous zirconium oxide (HZO) via thorough mixing of previously prepared CTet in methanol and stirred for 7 h at 27 °C.